From iron coordination compounds to metal oxide nanoparticles - Iacob, Mihail; Racles, Carmen; Tugui, Codrin; Stiubianu, George; Bele, Adrian; Sacarescu, Liviu; Timpu, Daniel; Cazacu, Maria (Beilstein Journal of Nanotechnology, 2016)
Various types, shapes and sizes of iron oxide nanoparticles were obtained depending on the nature of the precursor, preparation method and reaction conditions. The mixed valence trinuclear iron acetate, [Fe2IIIFeIIO(CH3COO)6(H2O)3]·2H2O (FeAc1), μ3-oxo trinuclear iron(III) acetate, [Fe3O(CH3COO)6(H2O)3]NO3∙4H2O (FeAc2), iron furoate, [Fe3O(C4H3OCOO)6(CH3OH)3]NO3∙2CH3OH (FeF), iron chromium furoate, FeCr2O(C4H3OCOO)6(CH3OH)3]NO3∙2CH3OH (FeCrF), and an iron complex with an original macromolecular ligand (FePAZ) were used as precursors for the corresponding oxide nanoparticles. Five series of nanoparticle samples were prepared employing either a classical thermal pathway (i.e., thermal decomposition in solution, solvothermal method, dry thermal decomposition/calcination) or using a nonconventional energy source (i.e., microwave or ultrasonic treatment) to convert precursors into iron oxides. The resulting materials were structurally characterized by wide-angle X-ray diffraction and Fourier transform infrared, Raman, energy-dispersive X-ray, and X-ray fluorescence spectroscopies, as well as thermogravimetric analysis. The morphology was characterized by transmission electron microscopy, atomic force microscopy and dynamic light scattering. The parameters were varied within each route to fine tune the size and shape of the formed nanoparticles.
Keywords: iron coordination compounds; mixed oxide nanoparticles; morphology control; nanoparticle shape control; optimization procedure